Effect of row arrangement on yield and monetary benefits in mulberry (Morusindica) + soybean (Glycine max) and mulberry + greengram (Phaseolus radiatus) intercropping - YADAV, B DAYAKAR; KUMAR, T NAGENDRA (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1989-91. to investigate the effect of inter cropping ’Kanva 2’ mulberry (Morns indica L.) + soybean [Glycine max (L.),Merr.]; and mulberry + greengram (Phaseolus radiatus L.) on yields of component crops, total land productivity and Monetary benefits under different row arrangements. Total yield was consistently greater in intercropping than in monocropping mainly due to increase in legume population between mulberry plants. Monetary benefits were consistantly higher in intercropping either in mulberry-soybean and or in mulberry + greengram than with the sole mulberry crop. With increase in plant population density both soybean and greengram showed decline in nodule population. Although intercropping mulberry with soybean or mulberry with greengram gave up to 40% higher overall yield advantage for the economic viability, mulberry + soybean or mulberry greengram row arrangement in 1 : 2 ratio proved better.